Regulamentações Ambientais e Governança Ambiental na promoção do Desenvolvimento Regional Sustentável: Um estudo nas microrregiões do Triângulo Mineiro e Alto Paranaíba - Silva, Rodrigo Cardoso e (2023)
The advances in the environmental impacts caused by the expansion of capitalism, an economic model based on the search for capital and the exploitation of natural resources, raises the need to discuss different forms of development that go hand in hand with the preservation of the environment. Environmental Governance presents the need for advances to take place based on partnerships between the private sector, society and the public sector. The forms of cooperation between different social actors seek greater participation in making the promotion of concepts such as Sustainable Regional Development viable. Here, the Environmental Regulations will also be analyzed as an institutional instrument of broad participation and that act to limit and control polluting agents. Thus, through a qualitative, exploratory and descriptive study, this research aims to analyze the situation of Environmental Regulations and Environmental Governance of the micro-regions of Triângulo Mineiro and Alto Paranaíba, in the promotion of Sustainable Regional Development, based on the SDGs proposed by the Agenda 2030. The studies in Triângulo Mineiro and Alto Paranaíba give the work a regional character and prove to be relevant in Minas Gerais, where this mesoregion has the highest per capita GDP within the state. The results showed that, in relation to environmental governance, there is inequality in terms of quality of governance between the regions studied, and that the two cities that concentrate the largest population, GDP and territory stood out in relation to the other regions studied. In addition, the levels of training, qualification, infrastructure, financing, participation of municipalities in partnerships with other levels of the federation (state and federal) were practically nil. With regard to Environmental Regulations, the regional profile demonstrated the existing concentration in regulations such as Subsidies (Market Instruments), which places Brazil on the same path as countries whose economy is based on recent industrialization. Regarding the SDGs, the profiles of governance and environmental regulations were aligned with SDG 3, SDG 6, SDG 7, SDG 9, SDG 12, and SDG 17, demonstrating the contribution of public authorities to the improvement of Regional Development indices sustainable in the region.